PEMANFAATAN PENGGUMPAL ALAMI EKSTRAK BUAH NENAS PADA PEMBUATAN TAHU DARI KEDELAI VARIETAS SLAMET UTILITY OF NATURAL COAGULANT EXTRACTED FROM PINEAPPLE IN TOFU PROCESSED FROM SLAMET VARIETY SOYBEAN - , Mustaufik; Sitoresmi, Ike (Pembangunan Pedesaan, 2005)
The study aimed at obtaining the appropriate concentration of natural coagulant from pineapple extract, extraction ratio for the best quality tofu, and comparison of tofu quality. Split-Split Plot Design was used with main plot were soybean variety (V1=Slamet and V2= import soybeans). The subplot was concentration of pineapple extract (K1= 1%, K2=1.5%, K3=2% v/v) and extraction ratio of soybeans and water (R1 = 1:6, R2 = 1:7, and R3 = 1:8 w/v). Results of the research showed that the optimum extract concentration in soybeans tofu processing was 1% (v/v) and the optimum ratio was 1:6 (w/v). Based on yield and texture, tofu from Slamet variety soybeans was better than the imported soybean but based on chemical composition, tofu from Slamet variety was relatively similar to tofu from import soybean. The best quality of soybeans tofu was produced from Slamet soybean with 1% (v/v) concentration of the extract and 1:6 (w/v) extraction ratio, with physicochemical and organoleptic characteristic as followed: 26.664% (db) protein, 5.797% (db) lipid, 0.9% (db) ash, 74.501% (wb) water, 9.696% (wb) or 96.96 g/1000 ml yield, 21.75 mm/g/dt texture, and 6.55 pH.